Characterization of Salophen Co(III) Acetate Ionophore for Nitrite Recognition. (10th October 2015) - Crespo, Gastón A.; Ghahraman Afshar, Majid; Barrabés, Noelia; Pawlak, Marcin; Bakker, Eric
ABSTRACT: The ionophore (salph)Co(III)OAc is used here for the first time as a recognition molecule for nitrite in lipophilic membranes. The nature of the recognition process is evaluated by UV-Vis, ATR-IR and potentiometry, while the purity of the compound is confirmed by LC-MS and cyclic voltammetry. Experimental evidence suggests a replacement of the acetate ligand by nitrite. The formation constant between (salph)Co(III)OAc and NO2 −, β∼10 8, is estimated potentiometrically with the sandwich membrane method. The analytical parameters, LOD∼3 μM, linear range of four orders of magnitude, stability over four days, and the selectivity over chloride (log KNO2, Cl POT ∼-4.1) are similar to previous ionophores for the same ion. Undiluted urine samples were spiked with incremental concentrations of nitrite to characterize the matrix effect. Beyond the observed analytical performance, we aim here to offer a rational study to understand an unconventional charged ionophore recognition process.